Influences of Donor Dopants on the Properties of PZT-PMS-PZN Piezoelectric Ceramics Sintered at Low Temperatures - Yoon, Seok-Jin; Choi, Ji-Won; Choi, Joo-Young; Wan, Dandan; Li, Qian; Yang, Ying (KOREAN PHYSICAL SOC, 2010)
0.90Ph(Zr(0.48)Ti(0.52))O(3)-0.05Pb(Mn(1/3)Sb(2/3))O(3)-0.05Pb(Zn(1/3)Nb(2/3))O(3) quaternary piezoelectric ceramics with CuO added were synthesized by using a conventional method at low sintering temperatures. CuO additive, 1.0 wt%, significantly improves the sinterability of 0.90PZT-0.05PMS-0.05PZN ceramics, lowering the sintering temperature to 900 degrees C and showing moderate electrical properties: d(33) = 306 pC/N, Q(m) = 997, k(p) = 53.6%, tan delta = 0.50%, and epsilon(T)(33) = 1351. To obtain more optimal piezoelectric properties, we selected Bi(2)O(3) and Nb(2)O(5) as donor dopants to introduce a softening effect. The crystal structure, micro-morphology and electrical properties were studied in terms of the Bi(2)O(3) and the Nb(2)O(5) contents. Our study demonstrates that Bi(2)O(3) is very effective in improving the piezoelectric properties, causing a significant enhancement in d(33) and k(p) values. Particularly, 0.75-wt%-Bi(2)O(3)-added 0.90PZT-0.05PMS-0.05PZN + 1.0 wt% CuO ceramics show excellent electrical properties: d(33) = 363 pC/N, Q(m) = 851, k(p) = 59.3%, tan delta = 0.38%, and epsilon(T)(33) = 1596. On the other hand, the effect of Nb(2)O(5) on the piezoelectric properties is very complicated, 0.50 wt% Nb(2)O(5) doped 0.90PZT-0.05PMS-0.05PZN + 1.0 wt% CuO ceramics have a remarkable improvement in k(p), value and maintain good electrical properties: d(33) = 300 pC/N, Q(m) = 971; k(p) = 58.4%, tan delta = 0.36%, and epsilon(T)(33) = 1332.
Keywords: SUBSTITUENTS